Characterization of a model of slide with bent leg in baseball - María Adela Ceballos-Rubio; Maury Rodríguez-Rodríguez (Universidad de Guantánamo, 2016)
The sliding movement with bent leg is an offensive action used to reach a base during the game. Its correct execution places a minor portion of the body to avoid the action of out before getting to base. Dividing this movement in phases makes easy detecting the error during its execution; hence this paper aims at evaluating the movement taking into consideration its characterization, and obtaining a model to contribute to its development for teaching. Three high performance sportsmen of the juvenile team of the Guantánamo province were filmed. Their movements were cinematically examined, divided into three phases according to the task, and a theoretical model was designed to easily detect technical errors in the evaluated subjects. During the cinematic analysis under these conditions, during the phase of descent of the body for support, it was detected the mechanism of approaching for support (in the vertical position) executed with some horizontal velocity, up to zero, since it is necessary to hold the upswing, which is why it becomes negative (sense change).